2008
DOI: 10.1016/j.envpol.2007.04.005
|View full text |Cite
|
Sign up to set email alerts
|

DDT uptake by arbuscular mycorrhizal alfalfa and depletion in soil as influenced by soil application of a non-ionic surfactant

Abstract: Combined colonization of alfalfa roots by an arbuscular mycorrhizal fungus and addition of non-ionic surfactant to the soil promoted root and shoot uptake and soil dissipation of DDT. AbstractA greenhouse pot experiment was conducted to investigate the colonization of alfalfa roots by the arbuscular mycorrhizal (AM) fungus Glomus etunicatum and application of the non-ionic surfactant Triton X-100 on DDT uptake by alfalfa and depletion in soil. Mycorrhizal colonization led to an increase in the accumulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 28 publications
(23 reference statements)
6
37
0
Order By: Relevance
“…In this study, it was observed that plants growth enhanced Hg evaporation from soil and mycorrhizal inoculation further promoted the enhancement. We speculate that the increase of Hg evaporation would contribute to the enhanced soil microbial activity since plant roots particularly inoculated roots can greatly increase soil microbial activity (Wu et al 2008). Mercury usually evaporates from soil to the air as the forms of organic Hg and Hg(0).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, it was observed that plants growth enhanced Hg evaporation from soil and mycorrhizal inoculation further promoted the enhancement. We speculate that the increase of Hg evaporation would contribute to the enhanced soil microbial activity since plant roots particularly inoculated roots can greatly increase soil microbial activity (Wu et al 2008). Mercury usually evaporates from soil to the air as the forms of organic Hg and Hg(0).…”
Section: Discussionmentioning
confidence: 99%
“…Mycorrhizal fungi can secrete organic materials and regulate root exudation into soil (Jones et al 2004), leading to a change in the quantity and composition of soil organic matter. Furthermore, mycorrhizal inoculation has been identified to result in an increase in soil microbial activity particularly in the rhizosphere soil (Wu et al 2008;Huang et al 2009), which can benefit the reduction of Hg(II) and Hg evaporation. Emission of Hg from soil is a significant source of Hg in the atmosphere, and comprehensive investigations are necessary to elucidate the role of mycorrhizal fungi in Hg circulation in biological environment.…”
Section: Discussionmentioning
confidence: 99%
“…The U-type distribution of the lower brominated PBDEs in the absence of inoculation might be due to a high degradation rate of BDE-209 in the root compartment (see data in Table S2) and limitation in transportation and plant uptake of the lower brominated PBDEs in the outer compartment, leading to a higher concentration of PBDEs in the soils in the root and outer compartments. The almost even distribution of PBDEs in inoculated rhizoboxes might be ascribed to the enhanced transportation of the lower brominated PBDEs in the soil as the result of mycorrhizal inoculation increasing root exudates or soil microbes, and a hyphal effect (Wu et al, 2008b;Joner and Leyval, 2003). However, these explanations are speculative and require further investigation.…”
Section: Bde-209 Debromination In Soilmentioning
confidence: 92%
“…Soil microbes are important for metabolism and degradation of halogenated organic contaminants in soils (Field and SierraAlvarez, 2008;Huang et al, 2011;Wu et al, 2008b) and likely play a key role in the degradation of BDE-209. PLFA analysis is a valuable method for tracking soil microbial profiles and determining soil microbial biomass (Hill et al, 2000;Joner et al, 2001).…”
mentioning
confidence: 99%
“…Most previous studies have found that AM fungi have positive effects on the dissipation of organic contaminants such as atrazine (Huang et al, 2007), PAHs (Joner et al, 2001;Joner and Leyval, 2003;Xu et al, 2006;Wu et al, 2008a), DDT (Wu et al, 2008b) and weathered p,p-DDE in soils (White et al, 2006), although no impact of AM fungi on PAH dissipation was observed by Binet et al (2000) and a depression in PAH dissipation in the presence of ectomycorrhizas (Joner et al, 2006;Genney et al, 2004) has also been reported. AM fungi may therefore play a critical role in the degradation of organic contaminants in soils.…”
Section: Introductionmentioning
confidence: 98%